2020
DOI: 10.31393/bba38-2020-09
|View full text |Cite
|
Sign up to set email alerts
|

General clinical and anthropometric parameters in patients with type 1 diabetes mellitus depending on the level of albumin in the urine

Abstract: Currently there are many experimental markers of diabetic nephropathy, but clinical practice focuses mainly on the presence of albuminuria, which usually manifests itself in both adults and children on average 5-7 years after the onset of diabetes. The aim of the study was to study the general clinical and anthropometric parameters in patients with type 1 diabetes mellitus (T1D) depending on the level of albumin in the urine. The study included 78 men and 62 women aged 22 to 26 years with T1D. The control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In a pairwise comparison of groups of men or women who took into account the level of cystatin C, with the corresponding sex groups of subjects, in which this biochemical indicator was not taken into account, found similar patterns and trends [12]. Thus, in the group of men with cystatin C levels <0.9 and in women with cystatin C levels >0.9, the percentage of patients with severe microvascular complications of diabetes increased with increasing albuminuria.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In a pairwise comparison of groups of men or women who took into account the level of cystatin C, with the corresponding sex groups of subjects, in which this biochemical indicator was not taken into account, found similar patterns and trends [12]. Thus, in the group of men with cystatin C levels <0.9 and in women with cystatin C levels >0.9, the percentage of patients with severe microvascular complications of diabetes increased with increasing albuminuria.…”
Section: Discussionmentioning
confidence: 84%
“…In our study, unfortunately, it was not possible to conduct a complete analysis of changes in general clinical and anthropometric parameters in patients with albuminuria at different levels of cystatin C, because the distribution in groups with proteinuria did not analyze women with cystatin C<0.9 and men with cystatin C>0.9 (the number of observations in these groups was only 1 and 3, respectively). For this reason, there is a limited explanation of why between patients with microalbuminuria, at different levels of cystatin C there are higher values of general clinical and anthropometric indicators at lower levels, while these indicators in general groups are characterized by diametrically opposite patterns (the value of these indicators increased as the level of albumin in the urine increases) [12].…”
Section: Discussionmentioning
confidence: 99%
“…In previous publications [13][14][15][16] it was found that in patients with T1D renal dysfunction in the early stages is manifested by impaired filtration function, characterized by increased serum levels of cystatin C and, accordingly, a decrease in GFR by cystatin C, and at later stages -a decrease in GFR, calculated on creatinine (by Cockcroft-Gault and CKD EPI), increase in urinary albumin, albumincreatinine ratio and serum creatinine. Accordingly, the assessment of the rate of change of glomerular filtration and its correlation analysis with classical markers of renal pathology made it possible to detail the diagnosis in patients with T1D at different stages of DN.…”
Section: Results Discussionmentioning
confidence: 99%